Disentangling comorbidity in chronic pain: A study in primary health care settings from India - Desai, Geetha (PLoS One, 2020)
OBJECTIVES: The study examined the prevalence, sociodemographic, and clinical correlates of chronic pain among primary care patients in the state of Kerala, India. It also examined the patterns and relationships of chronic physical and mental health conditions with chronic pain. METHODS: This study is a cross-sectional survey conducted among 7165 adult patients selected randomly by a multi-stage stratified design from 71 primary health centers. The questionnaires administered included Chronic pain screening questionnaire, self-reported Chronic physical health condition checklist, Patient Health Questionnaire-SADS, The Alcohol Use Disorders Identification Test, Fagerström Test for Nicotine Dependence, WHO Disability Assessment Schedule and WHOQOL- BREF for Quality/Satisfaction with Life. The prevalence and comorbid patterns of chronic pain were determined. Logistic regression analysis and generalized linear mixed-effects model was employed to examine the relationship of chronic pain to socio-demographic variables and examined physical and mental health conditions. RESULTS: A total of 1831 (27%) patients reported chronic pain. Among those with chronic pain, 28.3% reported no co-occurring chronic mental or physical illness, 35.3% reported one, and 36.3% reported multi-morbidity. In the multivariate analysis, patients with chronic pain when compared to those without had higher odds of being older, female, having lower education, not living with their family, greater disability, and poor satisfaction with life. Chronic pain was independently associated with both medical (hypertension, diabetes mellitus, tuberculosis, arthritis, and other medical illnesses) and mental health conditions (depressive disorders, anxiety disorders, and tobacco dependence). It showed a varying strength of association and additive effect with increasing number of co-occurring physical and mental illnesses. CONCLUSIONS: Chronic pain is a common condition among primary care attendees associated with significant burden of medical and mental health comorbidity. The findings highlight the need to incorporate treatment models that will ensure appropriate management to improve outcomes within the resource constraints.